Self Respect and Legal Awareness of State Administration Officials Towards Justice - Untoro, Untoro (Law Research Review Quarterly, 2016)
The fresearch objective is to find out how self respect and legal awareness of the State Administration Officer towards the decision of the State Administrative Court which has permanent legal force. The research alsp intended to find out how the influence of self respect and legal awareness of the State Administration Officer on the decision of the State Administrative Court which has legal power remains for the realization of justice. The research method used is the normative juridical approach. The results of research at the Jakarta, Bandung and Yogyakarta State Administrative Courts indicate that there is a request to the Chairperson of the State Administrative Court to order the defendant to carry out the decision. Means that the State Administration Officer in fulfilling the decision of the State Adm Court is not voluntary this matter because of the influence of self respect and legal awareness of the Administrative Officer. This situation influences the realization of justice and legal certainty in the settlement of state administrative disputes, whereas a decision besides having to be beneficial must also contain legal certainty. The absence of legal certainty will cause anxiety and the parties feel vacillated. That means the decision of the State Administrative Court is still floating execution, justice has not yet been realized in the settlement of state administration disputes in Indonesia which have the ideology of Pancasila and the predicate as a state of law.